Komitmen Pernikahan dan Komunikasi Interpersonal sebagai Prediktor Kesejahteraan Psikologis pada Wanita Bekerja yang Telah Menikah - Grace Bastian; Sri Aryanti Kristianingsih; Margaretta Erna Setianingrum (Kuras Institute, 2026)
Married working women face multiple role demands that can potentially impact their psychological well-being. Work pressures, family responsibilities, and relationship dynamics with their partners make marital quality a crucial factor in maintaining psychological health. This study aims to examine the role of marital commitment and interpersonal communication as predictors of psychological well-being in married working women. The research method used was a quantitative approach with a predictive design through a cross-sectional survey. The study participants were 318 married working women. Data were collected using a psychological well-being scale, a marital commitment scale, and an interpersonal communication scale. Data analysis used multiple linear regression. The results showed that marital commitment and interpersonal communication simultaneously significantly predict the psychological well-being of working women (R² = 0.092). This finding indicates that the higher the marital commitment and the more effective the interpersonal communication in the marital relationship, the better the perceived psychological well-being. Therefore, strengthening the quality of marital relationships through increased commitment and interpersonal communication is crucial in efforts to improve the psychological well-being of working women.